Synthesis and thermophysical properties of Ti3C2TX -based vanadium bromide redox flow for green energy storage - Hossain, Md Hasnat; Mohd Radzi, Mohd Amran; Zaed, Md Abu; Rahman, Saidur; Shafie, Suhaidi; Hossain, Md Showkot (IEEE, 2022)
Vanadium bromide redox flow batteries (V-Br RFB) have been created with new promising technologies for stationary renewable energy storage. Compared to previous redox flow battery systems, this technology is very efficient, inexpensive, and long-lasting. However, the low thermal conductivity, low diffusivity, high resistivity, high liquid density, and low energy efficiency of V-Br RFB need to be overcome. V-Br3 electrolytes containing MXene are being investigated in this work to increase thermal conductivity, decrease resistivity, and enhance diffusivity. The nanofluid based on V-Br3 electrolyte is tested with a varied MXene (Ti3C2Tx) content (0.25% wt, 0.50% wt, 0.75 % wt) at different temperatures. Thermal and electrochemical characterizations, such as FTIR, UV-Vis, SEM, and EDX are done. MXene's light transmission capacity is improved, the 2D layer structure was smooth, and electrolyte solutions were stable, according to FTIR, UV-Vis, SEM, and EDX. The highest value of thermal conductivity for an MXene-based electrolyte is raised versus a base solution by 53.6%, 70.3%, and 82.1% while the resistivity is lowered by 65.1%, 81.2%, and 81.9%. At 450C, 0.75% wt MXene provides the highest thermal conductivity enhancement of 82.1%. The study's improved physical, thermal, and electrochemical characterizations may aid future research into green energy storage technology, and it will help to meet the Sustainable Development Goals (SDGs).